PERSETERUAN DENISE DAN UYA KUYA: TRASH-TALKING SEBAGAI PERSONAL DIGITAL BRANDING - Muhamad Husni Mubarok (JOURNAL OF SCIENTIFIC COMMUNICATION (JSC), 2021)
The conflict between Denise Chariesta and Uya Kuya has become a byword for Indonesian netizens. This dispute certainly makes a question about what was being happened. Most of the netizens suppose that this case is merely a part of the setting. It is because Uya Kuya's image was already known as the king of pranks. As a newcomer in the entertainment industry, Denise was bravely against Uya Kuya by herself. Denise always uses her trashy words to humiliate and mock Uya Kuya’s family, who were well-known as top Indonesian celebrities. This study focuses on the case of their enmity by examining specifically the application of Denise’s Digital Personal Branding as her strategic self-marketing. The method in this study uses qualitative discourse analysis. This research shows that Denise uses trash-talking as her personal brand. It can be found in some aspects of personal branding such as the law of personality, the law of distinctiveness, the law of visibility, the law of unity, and the law of persistence. Mostly Denise uses the aggressive contexts of trash-talking in the form of insults, gossip, and various contexts such as satire, hyperbole, and sarcasm. Research also reveals that trash-talking as personal branding was effective as self-strategic marketing to increase someone's popularity. Recently, she becomes a popular celebrity and product endorser who was hunted by advertisers.